Utilization of wild Hevea germplasm in India: Long-term yield and growth of certain W x A hybrids - Reju M J; Abraham T; Mydin K K (Rubber Science, 2014)
One batch of 17 hybrids of Wickham (W) and Amazonian (A) parentage from six cross combinations were evaluated at the Central Experiment Station of the Rubber Research Institute of India. Yield of the clones in the BO-1 and BO-2 panels, combined yield from the two panels, summer yield, girth of the clones, biomass production and bole volume were evaluated. Heritability was moderate to high for both growth and yield parameters indicating scope for selection for the characters studied. Phenotypic variance and phenotypic coefficient of variation (PCV) showed values higher than the corresponding values for genotypic variance and genotypic coefficient of variation (GCV) for all the characters studied indicating the influence of environment on the characters. Secondary attributes like bole volume, biomass production and girth showed significant improvement in some of the hybrids (90/55, 90/109, 90/129 and 90/274) over the most popular and high yielding clone, RRII 105. Yield performance of these hybrids was on par with that of RRII 105. The hybrids which showed significantly improved bole volume and rubber yield comparable to RRII 105 may be designated as latex timber clones which could be utilized for further crop improvement programmes. Thus, without compromising on rubber yield it was possible to successfully develop W x A hybrids from divergent crosses in Hevea brasiliensis.
Keywords: Hevea breeding; Small-scale evaluation; Variability; W x A hybrids; Wild germplasm; Yield